Al-Qur’an Mastery Policy at IAIN Ponorogo: A Structural-Functional Analysis - Irma Rumtianing; Umar Faruq Thohir (Fakultas Syariah INSURI Ponorogo, 2026)
This study aims to analyze the implementation of the Decree of the Director-General of Islamic Education No. 6093 of 2020 concerning competency standards for Qur’an mastery, particularly in the teaching of the Qur’an at IAIN Ponorogo, using a structural-functional theoretical perspective. The research employs a qualitative evaluative approach, with data collected through document analysis, program evaluation reports, and observations of Qur'an learning activities. The findings reveal that implementing Qur'an teaching has significantly improved students' competencies in Qur'anic recitation, memorization, and comprehension. From a structural-functional perspective, the Qur'an learning program functions not only as an academic instrument but also as a mechanism for maintaining educational order and social stability within the institution. Nevertheless, challenges persist due to students' diverse educational backgrounds, which affect the uniformity of competency achievement. Therefore, this study recommends continuous evaluation, adaptive learning strategies, and differentiated instructional approaches to ensure the sustainability, relevance, and effectiveness of Qur'an teaching programs in responding to students' needs and institutional goals.